(3eQGLYI GdMSGHGJ aj HjFI GdJLGQI GdGdcJQhfjIs - (3Cjef eMeO UHQj TYHGf(B, (3fNGds ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2010)
(3CgejI OQGSI eQGLYI GdMSGHGJ aj HjFI GdJLGQI GdGdcJQhfjI(B-(3GdJLGQI GdGdcJQhfjI(B:(3GdedGeM hGdCNWGQ(B-(3GdCHYGO GdbGfhfjI ddJLGQI GdEdcJQhfjI(B-(3eNGWQ GdJLGQI GdEdcJQhfjI hJCejf GdeYdheGJ(B-(3COdI GdEKHGJ hELQGAGJ GdeQGLYI aj HjFI GdJLGQI GdGdcJQhfjI(B-(3CfhGY COdI GdEKHGJ aj VhA GdJTZjd GdGdcJQhfj ddHjGfGJ(B-(3COdI GdGKHGJ hELQGAGJ GdeQGLYI aj VhA GdJLGQI GdGdcJQhfjI(B-(3OhQ eQGLY GdMSGHGJ aj HjFI GdJLGQI GdGdcJQhfjI(B-(3NOeGJ GdJCcjO Ydi GdJLGQI GdGdcJQhfjI(B:(3NOeGJ GdKbI aj GdhjH(B-(3NOeGJ GdJCcjO Ydi eUOGbjI GdfXGe(B:(3NOeGJ GdKbI aj GdfXGes
(3GdeQGLY U(B.223s
Keywords: (3GdJLGQI GdGdcJQhfjIs; (3JObjb GdMSGHGJs; (3eQGLYI GdMSGHGJs